Readiness of Human Resources Facing Demographic Bonus and Professional Revolution in Indonesia - Muhammad Ikhsan Fahrezi; Imelda Hutasoit; Annisa Rahmadanita (Department of Public Administration, 2025)
Digitalization today has a significant impact on improving workforce competency standards. One aspect is the mastery and utilization of technology, which is now a benchmark for job providers in the recruitment process. Indonesia also faces the challenge of the demographic bonus phenomenon, where the number of productive workers increases but quality remains inadequate. Unlike previous studies that focused more on evaluating education as a factor shaping human resources, this study examines the relationship between the demographic bonus phenomenon and professional revolution as well as reasons behind low-quality human resources in Indonesia. The purpose of this research is to provide solutions for human resource readiness in facing challenges posed by both demographic bonuses and professional revolutions in Indonesia. The researcher used a Systematic Literature Review Method by analyzing 36 Scopus and Sinta accredited journal articles sourced from Scopus and Google Scholar metadata through Publish or Perish (PoP). The results show two main problems: first, low quality of Indonesian human resources indicated by poor thinking skills; second, ineffectiveness of vocational high school education in producing competent workers due to their inability to optimize relationships with industries or employers. To overcome these problems, it is suggested to optimize STEAM learning and revitalize vocational schools while changing study duration to five years for Diploma II equivalent graduates like Thailand's vocational education system.